2017
DOI: 10.4012/dmj.2016-252
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fiber content on flexural properties of glass fiber-reinforced polyamide-6 prepared by injection molding

Abstract: The use of non-metal clasp denture (NMCD) materials may seriously affect the remaining tissues because of the low rigidity of NMCD materials such as polyamides. The purpose of this study was to develop a high-rigidity glass fiber-reinforced thermoplastic (GFRTP) composed of E-glass fiber and polyamide-6 for NMCDs using an injection molding. The reinforcing effects of fiber on the flexural properties of GFRTPs were investigated using glass fiber content ranging from 0 to 50 mass%. Three-point bending tests indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
1
9
1
Order By: Relevance
“…However, all the results proved that nylon 6,6 make the interactions amongst the components stronger and this is proved by the solid-like behaviour of the composite at higher composition of glass fibre. The 30% 50% Glass fibre wt.% results obtained are in good agreement with previous literature concerning fiber reinforced composite (Garcia et al, 2018;Nagakura et al, 2017;Mortazavian and Fatemi, 2015).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…However, all the results proved that nylon 6,6 make the interactions amongst the components stronger and this is proved by the solid-like behaviour of the composite at higher composition of glass fibre. The 30% 50% Glass fibre wt.% results obtained are in good agreement with previous literature concerning fiber reinforced composite (Garcia et al, 2018;Nagakura et al, 2017;Mortazavian and Fatemi, 2015).…”
Section: Resultssupporting
confidence: 92%
“…There are many ejection systems used to eject the material like pin ejection, sleeve ejection, air ejection, which depending upon the nature of the product and mold. Normally the injection molding machine is divided into two parts provided with the mold between injection and clamping unit (Nagakura et al, 2017). The injection unit consists of a screw motor, a barrel, a hopper, a heater band, a stationary plate and aninjection nozzle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 ] The literature suggests that the nylon surface is more easily colonized by Candida species than that of PMMA,[ 30 ] which could clinically favor the appearance of pathologies, e.g., prosthetic stomatitis. [ 30 ] It has been reported that thermoplastic resins exhibit lower flexural strength,[ 46 47 48 49 ] elasticity modulus,[ 46 ] and hardness[ 47 ] in relation to heat-curing PMMA resin. Even when surface was treated with silica[ 34 46 ] and 4-META/MMA-TBB[ 46 ] resin, thermoplastic resins present great difficulty at bonding to the acrylic reliner, suggesting that relining procedures should only be performed in laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most effective reinforcement is yet to be determined (18). The glass fiber-reinforcement have showed promising results in previous studies (9,19,20).…”
Section: Introductionmentioning
confidence: 99%